Integrated retrograde and antegrade contact electro-impulse lithotripsy in the treatment of kidneys and ureteropelvic junction stones - A. V. Gudkov; V. S. Boshchenko; M. S. Lozovskiy; Ya. V. Shikunova (Вестник урологии, 2021)
Introduction. Nowadays, the tactics of removing stones from the kidneys and the ureteropelvic junction are widely covered and described in detail in modern guidelines. Determination of one or another treatment way depends on stone specific features and patient`s constitutional peculiarities. However, usage of percutaneous or retrograde access only does not always allow achieving a good result. In sophisticated cases, such as a large-size branchy renal stone, a “penetrated” stone in the ureter’s upper third, or some patient`s anatomic peculiarities, search for new ways to remove such stones with integrating accesses.Purpose of the study. To evaluate the removal efficiency of kidney stones and ureteropelvic junction by a combination of retrograde and percutaneous lithotripsy using electrical impulse energy. Materials and methods. In 2014-2019 in Siberian State Medical University Clinics (Tomsk, Russia), the integrated retrograde and percutaneous lithotripsy was applied in 26 cases to patients that had differently positioned kidneys’ and ureteropelvic junction stones. The treatment was based on the usage of the electro-impulse lithotriptor Urolith-105M (Lithotech Medical, Israel, MedLine LLP, Russia). In some cases, the laser lithotriptor Calculase II (Karl Storz, Germany) was also engaged. Result. The patients were aged from 25 to 76 (women - 69.2%). The calculus average size was 19.5 mm (varying from 5 to 51 mm). The calculus average density was 1229 HU (from 510 to 1720 HU). The operation average duration was 131 minutes (from 40 to 280 minutes). The incidence of complications was 3.84%. The complete calculus destruction occurred in 92.3% of cases. The overall response rate in re-operations reached up 100%.Conclusion. Integration of antegrade and retrograde accesses with use of the electro-impulse energy in removing complex stones from ureteropelvic junctions and kidneys proved to be an efficient method of treatment and demonstrated great results. Furthermore, this option of the single-step access to the stones is the only one possible in some cases when the extracorporeal lithotripsy is contraindicated, application of upfront surgery is quite risky, or endoscopic methods as an antegrade/retrograde mono-access are not effective .